Periodic Solutions of Multispecies Mutualism System with Infinite Delays - Wenbo Zhao; Caocuan Ma; Taotao Zheng; Xiao-Ke Sun (Abstract and Applied Analysis)
We studied the delayed periodic mutualism system with Gilpin-Ayala effect. Some new and interesting sufficient conditions are obtained to guarantee the existence of periodic solution for the multispecies mutualism system with infinite delays. Our method is based on Mawhin's coincidence degree. To the best knowledge of the authors, there is no paper considering the existence of periodic solutions for n-species mutualism system with infinite delays.